Influence of Swim Board Aids on Learning Freestyle Swimming Policy Techniques - Fauzi, Dira; Aminudin, Rizki; Nasution, Nana Suryana; Abdul Gani, Ruslan; Zinat Achmad , Irfan (Pelopor Publikasi Akademika, 2023)
The purpose of this study was to determine the Effect of Swim Board Aids on Learning Basic Freestyle Swimming Techniques in Class VII Students of SMP Negeri 5 West Karawang. The approach used in this study is a quantitative approach with experimental research methods. The population in this study was all students of SMPN 5 Karawang Barat class VII which amounted to 394 students. The study sample was taken using cluster random sampling technique. This research instrument uses freestyle swimming skill tests that have previously been made by previous researchers. Data analysis techniques using pretest posttest design. The result of the study was a pretest mean of 9.20 and a greater posttest mean = 12.07. The results of the paired sample t-test analysis with the data obtained are the significance value (2-tailed) = 0.000 less than the significance level (?) = 0.05, then H0 is rejected and H1 is accepted. So it can be concluded that learning using swim board aids can affect the improvement of basic freestyle swimming techniques at SMPN 5 West Karawang